Moral Enculturation Based Islamic Education Through Kitab Ta'lim Al-Muta'allim at Pesantren Bustanul Thullab Lamongan - Hepi Ikmal; Triana Rosalina Noor (LP. Ma'arif Janggan Magetan, 2024)
This qualitative case study aims to analyze the process of moral enculturation based on Islamic education through Kitab Ta'lim Al-Muta'allim at Pesantren Bustanul Thullab Lamongan. Data collection used interviews, observations, and documentation. The subjects are caregivers, leaders, pesantren administrators, and students selected by purposive sampling. The data were analyzed through data condensation, data presentation, and conclusion drawing, by using triangulation as verification. The findings indicate that the process of moral enculturation based on Islamic education through Kitab Ta'lim Al-Muta'allim at Pesantren Bustanul Thullab Lamongan is carried out through learning, role modeling, practice, and habituation. The learning process is conducted by Bandongan, Sorogan, and Musyawarah methods. Role modeling is implemented by having the kiai and teachers set an example for the students. Practical application is achieved through direct implementation in daily behavior. Habituation is carried out by encouraging students to integrate the values taught in Ta'lim Al-Muta'allim into their daily activities.